Formação em administração: interdisciplinaridade e institucionalismo - Tordino, Cláudio Antônio (2010)
Management Higher Education is an unique phenomenon in higher education after the Second World War. The spread of the belief that Administration conforms defined field of knowledge and the business management requires specific training prompted the institutionalization of knowledge and training and led to intense and extensive expansion of the area. Actually, the repertoire of knowledge that the management of contemporary corporations began to demand seems to require individuals whose capacity for assimilation, discrimination and power of synthesis are presented as extraordinary, to make the field appear as broad and multidisciplinary, for hosting knowledge from or drawn from different disciplines and areas of knowledge to be composed. This theoretical essay aims to explore the relationship between management higher education, interdisciplinarity and institutionalism, from the context that is engendered after the Second World War, in search for evidence the interdisciplinary nature of Administration and Institutional Theory, while discussing the difficulty of institutionalizing interdisciplinarity itself, including in such areas, given the disciplinary structure of higher education and academic background and interests that sustain it. The development of the study links the ideas so that the opening chapters point out the subject, problem and purpose, integrating them by describing the context, the theoretical framework and methodology under critical perspective. The chapters that follow, first of all, contemplate truth discourses about the knowledge, embracing the philosophical Nietzschean lenses and integrative and unifying perspective of this knowledge, interdisciplinary and transdisciplinary, sponsored by humanistic vision. Then, approaching the institutionalization process, through the lines emancipationist, historical, rational choice, sociological and discursive that explain it, put in perspective the academy for the ideals, ideas and discourses that produce or embodies and conveys to conform Higher Education as an institution, which allows to interpret management higher education as a speech of professional education. The final piece of work turns to the discussion of the possibility of training in critical management, even accepting the determinations derived from the mode of production, provided that the training of teachers and students embrace the interdisciplinary perspective, research and authorship as the fulcrum of the teaching-learning process. This path shows a potential of transition from multidisciplinary to interdisciplinary by anchoring training in social reality: it is the bearer of the applicant complexity of another kind of education